Case Report: Photodynamic therapy meets Chinese herbal medicine: a promising approach for advanced hypopharyngeal carcinoma - Lyu, Mingsheng; Wu, Huayang; Yu, Weixia; Zou, Hang; Ban, Chengjun; Wang, Lu; Wang, Hongwu; Wang, Linyang (Frontiers in Pharmacology, 2025)
Hypopharyngeal squamous cell carcinoma (HPSCC) continues to have the bleakest prognosis among head and neck cancers. Managing inoperable HPSCC, particularly in elderly patients, presents a complex therapeutic challenge. This case details an 84-year-old female with advanced recurrent HPSCC and a complex medical history was treated using photodynamic therapy (PDT) combined with Chinese herbal medicine (CHM). She was presented with a hemorrhagic mandibular mass. PDT was administered due to her inability to undergo surgery. Despite significant side effects such as erythema and swelling from PDT, these were effectively managed with the external application of the CHM formula Jiedu Zhitong Powder, which alleviated pain and inflammation. The treatment led to a decrease in tumor size, resolution of ulceration and hemorrhage, and improved hemoglobin levels, allowing the patient to be discharged. Regular follow-ups showed no recurrent bleeding, although she eventually succumbed to complications related to tumor progression 7 months post-treatment. This case highlights the potential benefits of integrating PDT with CHM in treating unresectable HPSCC. The successful management of PDT side effects with CHM could represent a promising avenue for enhancing patient tolerance and adherence to treatment in HPSCC cases.